Правові підстави визнання шлюбу та шлюбного договору фіктивними - Явор, О. А.; Yavor, O. A.; Кириченко, Т. С.; Kyrychenko, T. S. (ScienceRise: Juridical Science. - 2024. - № 1(27). - P. 36-43, 2024)
Метою даного дослідження є висвітлення проблем, пов’язаних з визнанням недійсними фіктивного шлюбу та фіктивного шлюбного договору на підставі комплексного аналізу законодавства України, спеціальної літератури та матеріалів судової практики.

The relevance of the research topic is connected with the fact that marriage and family relations are of the most importance for society. A person's health, well-being, ability to work, and his/her relationship with other members of society depend on family relationships. Today, it is important for the development of law to establish in people's minds the possibility and sometimes even the necessity of concluding marriage contracts, because it makes it possible to discover the reality of the intention of the other spouse, in order to avoid problems with the division of property. But this is possible only if there are available and understandable rules and the mutual desire of both parties. Conducting scientific research makes it possible to identify problematic points and propose more profitable legal mechanisms for the regulation of social relations. The most common and, at the same time, the most complex category are disputes over the recognition of marriage contracts as invalid. In the process of their consideration, many questions arise, the answers to which are missing both in the legislation and in the explanations of the Supreme Court of Ukraine. The situation is complicated by the fact that it is new for law enforcement practice and this category of cases has a certain specificity. In law enforcement, ambiguities arise when resolving cases of invalidity of marriage and application of the consequences of invalidity. There is no uniformity when deciding the issue of persons who have the right to challenge in court a fictitious marriage, another invalid marriage or the abuse of the right. Ambiguities concern the procedure for invalidating a dissolved marriage, concluded with a violation of the degree of consanguinity or in the presence of another registered marriage; approaches to the regulation of relations regarding the exercise of the rights of persons who are or were in an invalid marriage; regulation of contractual relations of persons who entered into civil and family legal relations with them. In the scientific literature, the criteria of invalidity, the grounds and consequences of the invalidity of a fictitious marriage, as well as the common and different between the invalidity of a marriage and an invalid agreement are not sufficiently presented, the concept and content of the invalidity of a marriage contract are not developed. It became necessary to distinguish between persons who are in an invalid marriage and persons whose marriage has been declared invalid. Persons who are in an invalid marriage should be recognized as fictitious spouses. The spouses (or one of them) know that they are in an invalid marriage, but before it is contested, there is a fiction of reality, that is, they (or one of them) create for all other persons the appearance of the reality of marriage, a false idea of marriage. However, according to the legislation of Ukraine, these persons are spouses. Persons whose marriage is declared invalid due to their (one of them) violation of the conditions for the validity of marriage and obstacles are unfaithful spouses. A fictitious marriage can be grounds for invalidating a marriage contract.

Целью данного исследования является освещение проблем, связанных с признанием недействительными фиктивного брака и фиктивного брачного договора на основании комплексного анализа законодательства Украины, специальной литературы и материалов судебной практики.
Keywords: фіктивний шлюб; шлюбний договір; правові підстави; визнання недійсним; fictitious marriage; marriage contract; legal grounds; annulment; фиктивный брак; брачный договор; правовые основания; признание недействительным